A hierarchical porous carbon aerogel embedded with small-sized TiO2 nanoparticles for high-performance Li–S batteries. (15th January 2023) - Shi, Chenguang; Huang, Junlong; Tang, Youchen; Cen, Zongheng; Wang, Zelin; Liu, Shaohong; Fu, Ruowen
Abstract: Lithium–sulfur (Li–S) batteries are one of the promising next-generation energy storage devices for meeting the growing energy demands. However, their commercial application have been hindered by several problems including the insulating nature of sulfur species, the shuttle effect of polysulfides, and the sizeable volumetric change of sulfur cathode upon cycling. Herein, a hierarchical porous carbon aerogel embedded with small-sized TiO2 nanoparticles (HPCA-TO) is prepared with polyacrylic acid grafted Ti3 C2 MXene as 2D template and TiO2 source, chitosan as carbon precursor. HPCA-TO is filtrated onto a commercial polypropylene separator as a functional interlayer towards the sulfur cathode. For the HPCA-TO, the small-sized polar TiO2 nanoparticles are beneficial for chemically reserving the soluble polysulfides, while the 2D carbon skeleton enables enhanced electrode conductivity, and the hierarchical porous structure can facilitate the ionic diffusion. As a result, the polysulfide shuttling is efficiently suppressed, and the conversion kinetics of polysulfides is largely enhanced. The Li–S batteries with the modified separators demonstrate a high initial discharge capacity (1439 mAh g −1 at 0.1 C) and excellent rate capability (502 mAh g −1 at 5 C). Graphical abstract: Image 1